2013
DOI: 10.1017/s1751731113000025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substitution of wheat starch by potato starch on the performance, digestive physiology and health of growing rabbits

Abstract: The goal of this research was to study the effect of the substitution of wheat starch by potato starch (PS) on the performance, health and digestion of growing rabbits. Three experimental diets were formulated with 0%, 7% and 14% PS (PS0, PS7 and PS14, respectively) and similar starch contents (22% dry matter basis), proteins and fibre. The three diets were administered to three groups of 48 rabbits from weaning (28 days) to slaughter (70 days), and growth and health measurements were made. Another 10 rabbits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A review of the literature concerning the dietary starch source in animals indicated that diets with corn starch (used in the form of raw materials) had the best growth performance in piglets, finishing pigs and yaks (Li et al, 2019). Compared with a wheat starch diet, the intake of potato starch had no effect on performance or digestive health of growing rabbits (Pinheiro et al, 2013). However, Yu et al (2019, 2020) showed that a pea starch diet (containing a high ratio of amylose) increased the average daily gain (ADG) of finishing pigs compared with corn starch and tapioca starch.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature concerning the dietary starch source in animals indicated that diets with corn starch (used in the form of raw materials) had the best growth performance in piglets, finishing pigs and yaks (Li et al, 2019). Compared with a wheat starch diet, the intake of potato starch had no effect on performance or digestive health of growing rabbits (Pinheiro et al, 2013). However, Yu et al (2019, 2020) showed that a pea starch diet (containing a high ratio of amylose) increased the average daily gain (ADG) of finishing pigs compared with corn starch and tapioca starch.…”
Section: Introductionmentioning
confidence: 99%